Congenital Granular Cell Tumor of the Newborn. A Case Report and Literature Review - Navas-Aparicio, María del Carmen (2022)
A congenital granular cell tumor is a benign and rare tumor of the oral cavity, which occurs exclusively in newborns and can cause, due to its size, a mechanical obstruction of the airway, and consequently, respiratory problems and feeding problems. Therefore, early diagnosis and treatment is important to promote the quality of life of both the patient and the parents. The purpose of this report is to (i) present the case of a patient diagnosed with congenital granular cell tumor (congenital epulis), its treatment and evolution and (ii) a review of the related literature because although its incidence is low, it is estimated that in 0.0006% of the cases the consequences are of important consideration if adequate management is not given.